Pharmacokinetics, Pharmacodynamics, and Safety of Lisinopril in Pediatric Kidney Transplant Patients: Implications for Starting Dose Selection. Issue 1 (2nd May 2015) - Trachtman, H; Frymoyer, A; Lewandowski, A; Greenbaum, LA; Feig, DI; Gipson, DS; Warady, BA; Goebel, JW; Schwartz, GJ; Lewis, K; Anand, R; Patel, UD; et al.
<x xml:space="preserve">Abstract</x> Hypertension in pediatric kidney transplant recipients contributes to long‐term graft loss, yet treatment options—including angiotensin‐converting enzyme inhibitors—are poorly characterized in this vulnerable population. We conducted a multicenter, open‐label pharmacokinetic (PK) study of daily oral lisinopril in 22 children (ages 7–17 years) with stable kidney transplant function. Standard noncompartmental PK analyses were performed at steady state. Effects on blood pressure were examined in lisinopril‐naïve patients (n = 13). Oral clearance declined in proportion to underlying kidney function; however, in patients with low estimated glomerular filtration rate (30–59 ml/min per 1.73m2), exposure (standardized to 0.1 mg/kg/day dose) was within the range reported previously in children without a kidney transplant. In lisinopril‐naïve patients, 85% and 77% had a ≥ 6 mmHg reduction in systolic and diastolic blood pressure, respectively. Lisinopril was well tolerated. Our study provides initial insight on lisinopril use in children with a kidney transplant, including starting dose considerations.